Information exchange model for remote consulting systems in the Russian Federation - Ilin Igor; Iliashenko Victoriia; Iliashenko Oksana (E3S Web of Conferences, 2019)
One of the most important and promising directions of introducing information and telecommunication technologies into the healthcare system in Russia is the development of a methodology for prolonged monitoring of the patient's condition and remote consultation by the attending physician. This is due to the fact that many diseases that hold leading positions in the structure of morbidity, disability and mortality of patients require active monitoring of the patient, including during the period between planned visits to the clinic. The creation of such systems can not only prevent medical errors, facilitate rapid response, but also helps to solve the most global problem in any chronic disease - poor adherence to treatment. Therefore, the development and implementation of a remote consultation system based on telemedicine technology will reduce the burden on the outpatient unit by reducing the need to visit a doctor and significantly improve the quality of medical care. However, the use of telemedicine technologies requires the existing business process reengineering of medicine center and process of information exchange between participants in this process - regional and federal medical centers. The article suggests the approach to forming information exchange model between federal and regional medical centers using telemedicine technologies for remote monitoring.